The Paradox of the Moderate Muslim Discourse: Subtyping Promotes Support for Anti-muslim Policies - Hakim, Nader H.; Zhao, Xian; Bharj, Natasha (Frontiers in Psychology, 2020)
Tolerant discourse in the U.S. has responded to heightened stereotyping of Muslims as violent by countering that “not all Muslims are terrorists.” This subtyping of Muslims—as some radical terrorists among mostly peaceful “moderates” —is meant to protect a positive image of the group, but leaves the original negative stereotype unchanged. We predicted that such discourse may paradoxically increase people’s support of anti-Muslim policies because the subtyping and its associated negative stereotypes justify hostile actions toward Muslims. In Study 1, subtyping predicted support for three anti-Muslim policies, but only among political moderates and conservatives. In Study 2, participants who were exposed to subtyping narratives expressed greater support for surveillance of Muslims in the U.S. The effect of subtyping narrative exposure was stronger on support for hawkish anti-terror policy when participants’ preexisting endorsement of subtyping was low. Irrespective of the well-meaning intentions of peaceful vs. radical subtyping, its expression can justify ongoing “War on Terror” policies. As the population of Muslims increases in North America, the intuition that most Muslims do not meet the negative stereotype may ironically reduce inclusion.